Obelia geniculata - Gil, Marta; Ramil, Fran (Zenodo, 2021)
Obelia geniculata (Linnaeus, 1758) Sertularia geniculata Linnaeus, 1758: 812. Laomedea geniculata – Broch 1914: 37. Obelia geniculata – Millard 1975: 229–230, fig. 75a–b. — Cornelius 1995: 301–303, fig. 70. — Calder 2012: 50–51, fig. 53. Material examined SOUTH ATLANTIC OCEAN •3 colonies, up to 5 mm high (all growing on brown algae, 2 colonies, with gonothecae); Vema Seamount, stn BT5; 31°37′16″– 31°36′58″ S, 8°22′37″– 8°23′06″ E; 71–94 m depth; 31 Jan. 2015; SEAFO-2015 leg.; SEAFO-2015-40317, SEAFO-2015-40327, SEAFO-2015-40768. Distribution Usually considered as a cosmopolitan species, with records from all oceans (Peña Cantero & García Carrascosa 2002), although absent from Antarctic waters (Peña Cantero 2004). In the Southeast Atlantic, it was recorded from Namibia (Broch 1914, as Laomedea geniculata (Linnaeus, 1758)), Vema Seamount (Millard 1966) and South Africa (Millard 1975). Its bathymetric distribution extends from the intertidal (Cornelius 1995) to 381 m (Gili et al. 1989). Published as part of Gil, Marta & Ramil, Fran, 2021, Hydroids (Cnidaria, Hydrozoa) from the Vema and Valdivia seamounts (SE Atlantic), pp. 49-96 in European Journal of Taxonomy 758 on page 66, DOI:10.5852/ejt.2021.758.1425, http://zenodo.org/record/5088125